2005
DOI: 10.1007/s00467-004-1759-7
|View full text |Cite
|
Sign up to set email alerts
|

The response to cyclophosphamide in steroid-sensitive nephrotic syndrome is influenced by polymorphic expression of glutathion-S-transferases-M1 and -P1

Abstract: Glutathione-S-transferases (GST) play a central role in the inactivation of toxic drugs like cyclophosphamide (CP). These enzymes depict several polymorphisms with altered activity, and it has been shown that different polymorphisms influence the risk of malignancies and the outcome after chemotherapy. To prove the hypothesis that CP efficacy in children with nephrotic syndrome is influenced by polymorphic expression of GSTs, the genotype of 26 patients was analyzed and correlated with the outcome after CP tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Conjugation of CPA metabolites involves several GST isoforms, some of which display increased levels in tumours. Enhanced detoxification of CPA metabolites would conceivably reduce the efficacy of chemotherapy; however, the clinical data available thus far do not provide supporting evidence of a correlation [114,115] . Aldehyde dehydrogenase isoforms are also involved in the detoxification of CPA and IFO metabolites [108] , and their overexpression in cultured cells decreases the sensitivity of cells to CPA and the related mafosamide [116,117] .…”
Section: Resistance To Alkylating Agentsmentioning
confidence: 93%
“…Conjugation of CPA metabolites involves several GST isoforms, some of which display increased levels in tumours. Enhanced detoxification of CPA metabolites would conceivably reduce the efficacy of chemotherapy; however, the clinical data available thus far do not provide supporting evidence of a correlation [114,115] . Aldehyde dehydrogenase isoforms are also involved in the detoxification of CPA and IFO metabolites [108] , and their overexpression in cultured cells decreases the sensitivity of cells to CPA and the related mafosamide [116,117] .…”
Section: Resistance To Alkylating Agentsmentioning
confidence: 93%
“…We observed a significant association of GSTP1 Ile105 polymorphism with a combination of GSTM1 null and GSTT1 null genotype and response to CP therapy in our study population. Studies by Vester et al have shown a significant effect of polymorphic expression of GST on the long-term remission rate after CP treatment in SSNS [18]. This study evaluated only 26 children with SSNS.…”
Section: Discussionmentioning
confidence: 97%
“…This study evaluated only 26 children with SSNS. It was observed that GSTM1 null genotype was shown to increase the efficacy of CP and that GSTP1 polymorphism was related to enhanced susceptibility to further relapses [18]. It was suggested that polymorphic expression of GSTM1 and P1 significantly influences the long-term remission rate, whereas GSTT1 genotype did not influence the outcome after CP treatment.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, in one study, the GSTP1 polymorphism (A>G) was associated with longer survival in breast cancer patients [17]. In contrast, children with steroid-sensitive nephrotic syndrome heterozygous or homozygous for GSTP1 variants, had worse remission than those with wild-type GSTP1 [18]. The latter observation is consistent with our results that patients with GSTP1 gene variants (heterozygous or homozygous) had a less remission (77.4% vs.84.4%, P =0.31)…”
Section: Discussionmentioning
confidence: 98%